Treatment Experiences Among Intimate Partner Violence Perpetrators: A Qualitative Analysis - Arvidsson, Moa (International journal of offender therapy and comparative criminology, 2024)
Intimate partner violence (IPV) is a global and widespread public health issue. Knowledge on what promotes individual-level reductions in risk for IPV recidivism is limited. In order to explore how group therapy influences the ability to obtain and sustain change, the objectives were to explore how IPV perpetrators make sense of and think about their experiences of group therapy and what their experiences are regarding needs of treatment for IPV perpetration. Six semi-structured interviews were conducted and analyzed with the qualitative method Interpretative Phenomenological Analysis. Two main themes were identified; “Experiences in group therapy” (subthemes: Ultimatum as a turning point; The guys as a powerful tool for change and Unfinished ending) and “Treatment needs” (subthemes: Violence as an addiction and Weakness as a strength). The findings highlight that group therapy is experienced positively, as well as difficulties that constitute obstacles, and need of further support after ending treatment.